Mengenali Isu Akuntabilitas Manajemen Dana Bantuan Operasional Sekolah (BOS) di Provinsi Papua - Cornelia Desiana Matani; Novalia H Bleskadit (Universitas Cenderawasih, 2022)
The study aims to identify issues of accountability for school operational assistance (BOS) in Papua Province. This study using a qualitative approach, namely content analysis. Content analysis is used to analyse the audited Regional Government Financial Reports (LKPD) and the Audit Results Report (LHP) as well as literature review of government regulations regarding BOS Funds. Based on the data analysis in 2019, the majority of audit findings in 22 of 29 regencies in Papua including the provincial government were related to mismanagement of the BOS fund. Planning issues such as the schools did not prepare their budget work plans. Thus, the school budget work plans not budgeted in the goverment Local Education Agency. As the result, The BOS Fund were not reported in the regional revenue and expenditure budget (APBD). The organizing issues such as there were no management team decision letters for the management team, no proper recording of assets, bookkeeping erors, no records of bank interests and administration fees as well as taxes charged on the bank accounts. The reporting issues that there were no expenditures otorisation letters and less orderly administrations for the disbursement requests. Therefore, the reporting of the BOS Fund in the LKPD were not properly disclosed. The schools’ accountability report was also a problem because schools fail to submit the BOS Fund report in time. This study shed light to accountability issues of BOS Fund mangement. Thus, the governments need to design practical assistance such as budget and financial management training for these schools management teams